Gypsum crust as a source of calcium for the consolidation of carbonate stones using a calcium phosphate-based consolidant. (15th July 2017) - Molina, Eduardo; Rueda-Quero, Lucía; Benavente, David; Burgos-Cara, Alejandro; Ruiz-Agudo, Encarnación; Cultrone, Giuseppe
Graphical abstract: Highlights: Treatment to carbonate stones altered by a gypsum crust by dibasic ammonium phosphate. Gypsum crust as a source of calcium by calcium phosphate-based consolidant. We have assessed the efficacy at different application times means cellulose poultice. Application time and water saturation of the poultice affect the amount of gypsum removed. Gypsum was eliminated after a single application treated during 60 minutes with DAP. Abstract: The high levels of atmospheric pollution in cities today are causing the decay of natural building stone, especially due to the formation of gypsum crusts on carbonate stones. For this reason we have assessed the efficacy of using the gypsum crust as an alternative source of calcium in the consolidation of building stone via the formation of calcium phosphates. Samples of Arenisca Ronda (southern Spain) were altered to develop a gypsum crust on the surface for subsequent application of a cellulose poultice with a solution of dibasic ammonium phosphate 3 M (DAP) at different application times. The best results were obtained by the samples treated for 60 min and they have indicated that the application time and the water saturation degree of the poultice affect the amount of gypsum removed and the quantity of fissures on the consolidant film. On the other hand, the DAP concentration of the solution and the pH controlled the calcium phosphate precipitation phases. The habit of the calcium phosphate crystals evolve over the time tending to a homogenization of the consolidant film. This procedure offers an important alternative for the treatment of altered carbonate stones, in which the stone can be cleaned and consolidated in a single application.